Risk Factors for Patient–Ventilator Asynchrony and Its Impact on Clinical Outcomes: Analytics Based on Deep Learning Algorithm - Ge, Huiqing; Duan, Kailiang; Wang, Jimei; Jiang, Liuqing; Zhang, Lingwei; Zhou, Yuhan; Fang, Luping; Heunks, Leo M. A.; Pan, Qing; Zhang, Zhongheng (Frontiers in Medicine, 2020)
Background and objectives: patient-ventilator asynchronies (PVA) are common in mechanically ventilated patients. However, the epidemiology of PVAs and its impact on clinical outcome remains controversial. The current study aims to evaluate the epidemiology, risk factors of PVAs, and their impact on clinical outcomes using big data analytics. Methods: the study was conducted in a tertiary care hospital; all patients with mechanical ventilation from June to December 2019 were included for analysis. Negative binomial regression and distributed lag non-linear models (DLNM) were used to explore risk factors for PVAs. PVAs were included as a time-varying covariate into Cox regression models to investigate its influence on the hazard of mortality and ventilator associated events (VAE). Results: A total of 146 patients involving 50,124 hours and 51,451,138 respiratory cycles were analyzed. The overall mortality rate was 15.6%. Double triggering was less likely to occur during day hours (RR: 0.88; 95% CI: 0.85 – 0.90; p < 0.001) and occurred most frequently in PCV mode (median: 3; IQR: 1 – 9 per hour). Ineffective effort was more likely to occur during day time (RR: 1.09; 95% CI: 1.05 – 1.13; p < 0.001) and occurred most frequently in PSV mode (median: 8; IQR: 2 – 29 per hour). The effect of sedatives and analgesics showed temporal patterns in DLNM. PVAs were not associated mortality and VAE in Cox regression models with time-varying covariates. Conclusions: Our study showed that counts of PVAs were significantly influenced by time of the day, ventilation mode, ventilation settings (e.g. tidal volume, plateau pressure), and sedatives and analgesics. However, PVAs were not associated with the hazard of VAE or mortality after adjusting for protective ventilation strategies such as tidal volume, plateau pressure and PEEP.